2015
DOI: 10.1200/jco.2015.62.7273
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Allogeneic Transplantation for Older Patients With Acute Myeloid Leukemia in First Complete Remission Using a Reduced-Intensity Conditioning Regimen: Results From Cancer and Leukemia Group B 100103 (Alliance for Clinical Trials in Oncology)/Blood and Marrow Transplant Clinical Trial Network 0502

Abstract: Reduced-intensity conditioning HSCT to maintain remission in selected older patients with AML is relatively well tolerated and appears to provide superior outcomes when compared with historical patients treated without HSCT. GVHD and NRM rates were lower than expected. Future transplantation studies in these patients should focus on further reducing the risk of relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
89
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(101 citation statements)
references
References 37 publications
11
89
1
Order By: Relevance
“…104 A prospective multicenter phase II study examined the efficacy of RIC allogeneic HCT in older patients (range, 60-74 years) with AML in first CR (n=114). 105 After allogeneic HCT, DFS and OS at 2 years were 42% (95% CI, 33%-52%) and 48% (95% CI, 39%-58%), respectively, for the entire group. 105 A time-dependent analysis of 4 successive prospective HOVON/SAKK AML trials examined data from patients aged ≥60 years who experienced a first CR after induction chemotherapy (n=640).…”
Section: Postremission Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…104 A prospective multicenter phase II study examined the efficacy of RIC allogeneic HCT in older patients (range, 60-74 years) with AML in first CR (n=114). 105 After allogeneic HCT, DFS and OS at 2 years were 42% (95% CI, 33%-52%) and 48% (95% CI, 39%-58%), respectively, for the entire group. 105 A time-dependent analysis of 4 successive prospective HOVON/SAKK AML trials examined data from patients aged ≥60 years who experienced a first CR after induction chemotherapy (n=640).…”
Section: Postremission Therapymentioning
confidence: 99%
“…105 After allogeneic HCT, DFS and OS at 2 years were 42% (95% CI, 33%-52%) and 48% (95% CI, 39%-58%), respectively, for the entire group. 105 A time-dependent analysis of 4 successive prospective HOVON/SAKK AML trials examined data from patients aged ≥60 years who experienced a first CR after induction chemotherapy (n=640). 106 For patients who received allogeneic HCT as postremission therapy (n=97), the 5-year OS rate was 35% (95% CI, 25%-44%).…”
Section: Postremission Therapymentioning
confidence: 99%
“…[22][23][24] Similarly, a prospective phase 2 study by Cancer and Leukemia Group B showed that patients with a median age of 65 years had leukemia-free survival (LFS) and OS after 2 years of 42%, and that HCT was overall well tolerated, with superior outcomes when compared with nontransplant treatment. 25 Although outcomes of patients with all subtypes of AML after MAC and RIC are well described, the outcomes of patients who are specifically transplanted with sAML are not. Thus, this study by the Acute Leukemia Working Party (ALWP) of the European Society for Blood and Marrow Transplant (EBMT) network was undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…A multi-institutional trial of reduced intensity fludarabine and busulfan described encouraging low rates of 2-year NRM of 15% and 2-year survival of 48% for AML in first remission. 14 Sorror et al reported favorable 5-year OS of 35% after nonmyeloablative allogeneic for prospectively enrolled patients $60 years.…”
Section: Older Age and Transplant Utilizationmentioning
confidence: 99%